A Molecular Rationale of Shock Absorption and Self-Healing in a Biomimetic Apatite-Collagen Composite under Mechanical Load - Zahn, Dirk (Angewandte Chemie International Edition, 2010)
Once bitten: Compression along the c axis of apatite–collagen composites (see picture), such as that on tooth enamel during biting, reveals a molecular mechanism that accounts for the steel-like characteristics of these composites. Simulations reveal that before eventual failure, inelastic deformation is initiated near the collagen molecules followed by pseudo-elastic deformation. The composite may undergo self-healing after release of the mechanical load.
EAM Import::2019-03-13